Parents’ perspectives on homework practices in pre-primary school children in Tanzania: a phenomenological analysis (Educational Dimension, 2024)
This study investigated parents’ practices in helping pre-primary school children with homework in Dodoma City, Tanzania. The study was guided by two specific objectives: to investigate the learning opportunities perceived by parents and the perceived challenges. The study involved 23 respondents from 15 families in Dodoma City, Tanzania. A convenience sampling technique was used to obtain families and parents. A phenomenology design was used, and semi-structured interviews were conducted to obtain data from the respondents. Thematic analysis was employed to analyse the collected data. The study revealed several learning opportunities among children, such as fostering child-parent relationships, knowing and monitoring children’s academic progress, and reinforcing learning and discipline among children. Also, several challenges were revealed from the study findings, including time-consuming, stressful and tedious activities for parents and children. The study concludes that parents’ involvement in children’s homework is vital for improving child-parent relationships and monitoring children’s academic progress. Therefore, the study recommends that teachers provide clear guidance to parents on assisting children with homework. Further, school administrators should encourage parents to participate in their children's education to improve their learning.
Keywords: homework; pre-primary education; early childhood education; parental involvement; learning attainment